Using a Multifaceted Quality Improvement Initiative to Reverse the Rising Trend of Cesarean Births. Issue 7 (July 2018) - Ogunyemi, Dotun; McGlynn, Sara; Ronk, Anne; Knudsen, Patricia; Andrews-Johnson, Tonyie; Raczkiewicz, Angeline; Jovanovski, Andrew; Kaur, Sangeeta; Dykowski, Mark; Redman, Mark; Bahado-Singh, Ray
Abstract : (Abstracted from J Matern Fetal Neonatal Med 2018;31:567–579) One in 3 births in the United States is a cesarean delivery, which is associated with both increased morbidity and higher health care costs than vaginal delivery. In the United States, the primary cesarean delivery rate is approximately 17%, whereas the nulliparous term singleton vertex (NTSV) rate is 26%.